2007
DOI: 10.1375/twin.10.5.749
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Body Mass Index: A Comparison Between The Netherlands and Spain

Abstract: A high body mass index (BMI) is commonly used as an index of overweight and obesity. There is persistent evidence of high heritability for variation in BMI, but the effects of common environment appear inconsistent across different European countries. Our objective was to compare genetic and environmental effects on BMI in a sample of twins from two different European countries with distinct population and cultural backgrounds. We analysed data of adult female twins from the Netherlands Twin Register (222 mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
(37 reference statements)
3
21
0
Order By: Relevance
“…Third, we treated BMI as a continuous or quantitative measure and did not take into account the clinically relevant differences within the range of BMI’s observed in this sample. Though this is a more statistically powerful approach and is consistent with previous studies [Schousboe et al, 2003; Ordonana et al, 2007; Cornes et al, 2007; Silventoinen et al, 2007; Franz et al, 2007; Pietilainen et al, 1999, 2002; Maes et al, 1997] there has been a suggestion that shared environmental influences are relevant to the clinical classifications of overweight and obese [Nelson et al, 2006]. Lastly, though sample sizes were large in the current study, our results did not support previous reports of non-additive genetic contributions to BMI.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Third, we treated BMI as a continuous or quantitative measure and did not take into account the clinically relevant differences within the range of BMI’s observed in this sample. Though this is a more statistically powerful approach and is consistent with previous studies [Schousboe et al, 2003; Ordonana et al, 2007; Cornes et al, 2007; Silventoinen et al, 2007; Franz et al, 2007; Pietilainen et al, 1999, 2002; Maes et al, 1997] there has been a suggestion that shared environmental influences are relevant to the clinical classifications of overweight and obese [Nelson et al, 2006]. Lastly, though sample sizes were large in the current study, our results did not support previous reports of non-additive genetic contributions to BMI.…”
Section: Discussionsupporting
confidence: 64%
“…Since the early adoption studies by Stunkard and colleagues [Stunkard et al, 1986; Sorensen et al, 1989], familial resemblance for body mass has been shown to be largely due to heritable factors rather than environmental influences shared by siblings [Sorensen et al 1992; Cornes et al, 2007; Maes et al, 1997; Schousboe et al, 2003; Hewitt, 1997; Wardle et al, 2008; Hur et al, 2007]. Estimates of the total genetic contribution to observed variation in BMI have ranged from 0.30 to over 0.90, varying as a function of study design and age [Schousboe et al, 2003; Ordonana et al, 2007; Cornes et al, 2007; Silventoinen et al, 2007; Franz et al, 2007; Pietilainen et al, 1999, 2002; Maes et al, 1997; Wardle et al, 2008; Hur et al, 2007]. Although heritability estimates are medium to large at any single age, the extent to which genetic contributions correlate across ages is less than perfect, indicating possible age-related changes in expressed genetic effects [Franz et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…IQ data are available from different studies that examined children at ages 5 through 18 years who took part in studies of the Netherlands Twin Register at the VU University Amsterdam 2 and consist of longitudinal measures of psychometric IQ in four groups of twins and include a high scoring group (N 1 = 1951, N 2 = 587, N 3 = 1080, N 4 = 852), their siblings (N 1 = 95, N 2 = 260, N 3 = 53) and parents (N 2 = 350) at twin's ages 5, 7, 9, 10, 12, 15, 17, and 18 years. Phenotypic correlations between IQ measures and educational attainment and educational level are substantial and all measures show moderate (IQ in early childhood) to substantial heritability (all other measures).…”
Section: Genetic Analysis Of Longitudinally Measured Iq Educational mentioning
confidence: 99%
“…Systolic BP (SBP) and diastolic BP (DBP) as well as height and weight were measured at the induction physical examination. Body mass index (BMI) was used as the index of general obesity and calculated as weight(kg)/ height(m) 2 . Quantitative genetic modeling was performed using Mx software.…”
Section: Department Of Psychology Center Of Excellence In Behavior Gmentioning
confidence: 99%
“…74) of BMI among identical twins who are raised apart from one another (Price and Gottesman 1991; Stunkard et al 1986) Jacobson and Rowe (1998), using data from Add Health, estimate the heritability of BMI among male adolescents to be roughly .80 (A = .65, D = .16) with no shared environmental influences; in this study, roughly 80% of the variation in BMI was shown to be genetically oriented. Other BMI heritability estimates have ranged between 0.30 to more than 0.90, varying as a function of study design and age (Schousboe et al, 2003; Ordonana et al, 2007; Cornes, Zhu, and Martin 2007; Silventoinen et al, 2007; Franz et al, 2007; Haberstick et al 2010). …”
mentioning
confidence: 99%